2005
DOI: 10.1007/s00213-005-0125-1
|View full text |Cite
|
Sign up to set email alerts
|

Preexposure during or following adolescence differently affects nicotine-rewarding properties in adult rats

Abstract: Exposure following the adolescent period might diminish the risk to develop nicotine dependence. As for human implications, findings are consistent with a reduced vulnerability to nicotine addiction in people who start smoking late in their life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
49
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 53 publications
8
49
2
Order By: Relevance
“…This is not in accord with earlier studies showing reduced neurobehavioral plasticity in adult animals Adriani et al, 2003Adriani et al, , 2006. In these studies, nicotine treatment increased nicotine self-administration in periadolescent rats but not in postadolescent rats, and was associated with increased expression of distinct subunits of acetylcholine receptor in adult rats, downregulation of striatal AMPA receptors in striatum in adult mice, and longterm disruption of locomotor habituation in mice.…”
Section: Discussioncontrasting
confidence: 84%
“…This is not in accord with earlier studies showing reduced neurobehavioral plasticity in adult animals Adriani et al, 2003Adriani et al, , 2006. In these studies, nicotine treatment increased nicotine self-administration in periadolescent rats but not in postadolescent rats, and was associated with increased expression of distinct subunits of acetylcholine receptor in adult rats, downregulation of striatal AMPA receptors in striatum in adult mice, and longterm disruption of locomotor habituation in mice.…”
Section: Discussioncontrasting
confidence: 84%
“…Bracken et al (2011) recently confirmed that adolescent nicotine induces adult nicotine sensitization in the rat. In addition to lasting changes in sensitization, adolescent nicotine leads to enhanced self-administration of nicotine in adult mice (Adriani et al, 2006) and rats ; this, however, was not confirmed by Weaver et al, (2012) in rats.…”
Section: Addiction-related Behavioral Changesmentioning
confidence: 84%
“…Rats that were exposed to caffeine in their drinking water were more likely to acquire the nicotine self-administration response, acquired this behavior more rapidly, and took larger amounts of nicotine than rats that never received caffeine (Shoaib et al, 1999); but, since caffeine exposure was maintained both before and during the acquisition training in this study, it is not known how much these effects were due to a history of caffeine exposure, as opposed to having caffeine in the system at the same time as nicotine. Preexposure to nicotine in post-adolescent rats produced a tolerance-like effect, preventing the development of conditioned place preference when a distinctive environment was associated with 0.3 mg/kg nicotine, but not a higher dose (0.6 mg/kg; Adriani et al, 2006).…”
Section: Discussionmentioning
confidence: 98%